Multiplexing single-beam coherent anti-stokes Raman spectroscopy with heterodyne detection - Wipfler, Alexander; Buckup, Tiago; Motzkus, Marcus (Applied physics letters, 2012)
Multiplex detection of single beam coherent anti-Stokes Raman spectra is achieved by phase shaping of a narrow gate probe. The spectrally resolved signal is amplified via a local oscillator derived from the same single beam and is disentangled via double quadrature spectral interferometry. Spectral resolution and spectral range are defined by the width and position of the phase gate, which can be easily set by a femtosecond pulse shaper. Such phase-only multiplexed single beam coherent anti-Stokes Raman spectroscopy is demonstrated for simple molecules and is combined with Raman line reconstruction methods to obtain dispersion free Raman resonances.